2022
DOI: 10.1007/s00259-022-05708-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive imaging of tau-targeted probe uptake by whole brain multi-spectral optoacoustic tomography

Abstract: Purpose Abnormal tau accumulation within the brain plays an important role in tauopathies such as Alzheimer’s disease and frontotemporal dementia. High-resolution imaging of tau deposits at the whole-brain scale in animal disease models is highly desired. Methods We approached this challenge by non-invasively imaging the brains of P301L mice of 4-repeat tau with concurrent volumetric multi-spectral optoacoustic tomography (vMSOT) at ~ 115 μm spatial resolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 103 publications
0
26
0
Order By: Relevance
“…93 ) from PMOD. VOI analysis of 15 brain regions was performed using the embedded Mouse VOI atlas (Ma-Benveniste-Mirrione) in PMOD as in standard microPET data analysis procedure 15,94 . Specifically, time course of regional AOI987 absorbance (a.u.)…”
Section: Co-registration With Mri and Volume-of-interest Analysis Of ...mentioning
confidence: 99%
“…93 ) from PMOD. VOI analysis of 15 brain regions was performed using the embedded Mouse VOI atlas (Ma-Benveniste-Mirrione) in PMOD as in standard microPET data analysis procedure 15,94 . Specifically, time course of regional AOI987 absorbance (a.u.)…”
Section: Co-registration With Mri and Volume-of-interest Analysis Of ...mentioning
confidence: 99%
“… 250 Further, whole-brain targeted imaging of tau deposits, also a factor in diagnosing Alzheimer’s and dementia, was shown using pyridinyl-butadienyl-benzothiazole derivative PBB5. 251 An extensive review of molecular imaging of various brain diseases using PAI was recently published. 252 …”
Section: Molecular Photoacoustic Imagingmentioning
confidence: 99%
“…Ezura et al (2021) compared differential binding of [ 18 F]THK5351 to different tauopathies and found that high [ 18 F]THK5351 uptake was detected in the precentral and postcentral gyri of CBD patients, in the midbrain of PSP patients and in the parahippocampal gyri of AD patients compared to healthy controls, clearly distinguishing different tauopathies. In vivo imaging using [ 11 C]PBB3 showed the detection of tau inclusions in the brain stem of PS19 and cortical and hippocampal regions of the rTg4510 mouse model of FTD (Maruyama et al, 2013;Ishikawa et al, 2018;Ni et al, 2018;Vagenknecht et al, 2022). A disadvantage of radiolabeled [ 11 C]PBB3 is the insufficient dynamic range, clearance rate and off-target binding in the basal ganglia (Okamura et al, 2018).…”
Section: In Vivomentioning
confidence: 99%